2008
DOI: 10.1111/j.1095-8649.2008.01984.x
|View full text |Cite
|
Sign up to set email alerts
|

Different ocean and climate factors control the marine survival of wild and hatchery Atlantic salmon Salmo salar in the north‐east Atlantic Ocean

Abstract: The influence of climate and ocean conditions on the marine survival of 1SW Irish Atlantic salmon Salmo salar was explored. Generalized additive models (GAM) explained c. 85% of the observed variations in survival and provided an insight into the mechanisms involved. A positive phase of the North Atlantic oscillation (NAO) and increasing sea surface temperatures (SST) were linked to a decrease in S. salar survival. The NAO in the winter before the smolts migration contributed to c. 70% of the deviance in marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 64 publications
1
36
0
Order By: Relevance
“…Annual herring abundance and the mean catch weight of salmon were the main factors causing variation in marine survival. Many earlier studies have shown that the marine survival of salmon is controlled by both climatic factors and prey fish abundance (Friedland et al, 1993(Friedland et al, , 1998(Friedland et al, , 2000(Friedland et al, , 2009Kallio-Nyberg et al, 2004, 2006Peyronnet et al, 2008).…”
Section: Hatchery Rearing and Marine Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Annual herring abundance and the mean catch weight of salmon were the main factors causing variation in marine survival. Many earlier studies have shown that the marine survival of salmon is controlled by both climatic factors and prey fish abundance (Friedland et al, 1993(Friedland et al, , 1998(Friedland et al, , 2000(Friedland et al, , 2009Kallio-Nyberg et al, 2004, 2006Peyronnet et al, 2008).…”
Section: Hatchery Rearing and Marine Survivalmentioning
confidence: 99%
“…The variation in growth and survival has been linked either to environmental variation (Friedland et al, 1993(Friedland et al, , 2000Jonsson and Jonsson, 2004;Kallio-Nyberg et al, 2004, 2006Peyronnet et al, 2007Peyronnet et al, , 2008 or human-induced selection due to fishing or domestication (McGinnity et al, 2007;Quinn et al, 2006). There is abundant evidence of the detrimental effects of large-scale farming and stocking of hatchery-reared salmon stocks in the Pacific and Atlantic Oceans (Hindar et al, 1991;Fleming et al, 1996Fleming et al, , 2000Jonsson, 1997;McGinnity et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Oceanic variations influence salmon growth and survival (Scarnecchia 1984, Peyronnet et al 2008, and more rapid growth of smolts in their first summer may increase both survival and the ratio of grilse to 2SW salmon (Scarnecchia et al 1991, Friedland & Haas 1996, Peyronnet et al 2007). The similarity in survival and sea age among release groups observed in the present study indicates that the conditions in sea did not change significantly from June to August 2005, and the reduction in the size of the recaptured fish with time of release was very low compared to the 20% weight loss observed in a sea-ranching experiment in which the time of release ranged from May to early June (Skilbrei & Wennevik 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a detailed regional analysis of southern European salmon survival in relation to the NAO, Peyronnet et al (2008) assessed two wild and nine hatchery populations from rivers in western Ireland since the early 1980s. They showed the importance of the NAO to adult survival and recruitment, and especially the intense impact of the winter NAO prior to the spring smolt migration to sea.…”
Section: Amo Departurementioning
confidence: 99%